Manajemen Pembinaan Karir Sumber Daya Manusia dalam Pendidikan Islam - Riza Azhari; Abdul Halim Wicaksono (At-Ta'dib, 2017)
Implementation of Career Development Management of human resources in Islamic boarding school have been implemented, but not as expected yet. One factor that influences the job satisfaction of teachers or staff is career development. Obvious of career in the organization will be able to improve the motivation of employees in carrying out their work, thus creating a sense of satisfaction. Every human resource is given the opportunity to develop career and ability optimally. Career goal is the further position of individuals/ employee in their work. Such conditions require organizations to undertake career coaching for workers, which must be implemented on a planned and sustainable basis. In other words, career coaching is one of human resources (HR) management activities, should be implemented as a formal activity that is done in an integrated manner with other human resources (HR) activities. While career planning that planned by employees and organizations with regard to employee career, especially regarding the preparation that must be met by an employee to achieve certain career goals. The point is employee career planning must be done by both parties, employee and organization. If not, then employee career planning will not produce a good plan and realistic.